The Influence of Leadership and Professionalism on The Performance of The Education Service Depok City West Java Province - Imaniyati, Astri; Syafri, Wirman; Ruhana, Faria; W. Kawuryan, Megandaru; Hutasoit, Imelda (Pelopor Publikasi Akademika, 2025)
The Depok City Education Office faces challenges in improving work effectiveness, including low teacher competency, high absenteeism, and suboptimal organizational performance. This study aims to analyze the influence of leadership and professionalism on organizational performance, both individually and collectively, addressing key factors to enhance institutional effectiveness. A descriptive quantitative method was used, involving a sample of 298 respondents from a population of 1,170, with data analyzed statistically. The findings reveal that professionalism has a stronger impact on performance (57.4%) compared to leadership (37.3%), and together, they account for 62.9% of the variation in performance, while the remaining 37.1% is influenced by external factors. The change agent dimension of leadership emerged as the most significant, while the direction setter role was less impactful. Within professionalism, the knowledge dimension was highly influential, whereas productivity had the least impact. The study concludes that enhancing leadership and professionalism, with a focus on adaptability and conceptual knowledge, is essential for addressing performance issues. These results provide actionable insights to improve the effectiveness of the Depok City Education Office and similar organizations.